Study of aerobic granular sludge stability in a continuous-flow membrane bioreactor. (January 2016) - Corsino, S.F.; Campo, R.; Di Bella, G.; Torregrossa, M.; Viviani, G.
Highlights: The potentiality of continuous AGS is confirmed by experimental data. The feast/famine alternation is a key issue in continuous flow for AGS maintenance. EPSs had a key role in granules strength. Hydraulic selection pressure is necessary to ensure flocculent sludge washout. A correct management of granular sludge withdrawal should improve membrane fouling. Abstract: A granular continuous-flow membrane bioreactor with a novel hydrodynamic configuration was developed to evaluate the stability of aerobic granular sludge (AGS). Under continuous-flow operation (Period I), AGS rapidly lost their structural integrity resulting in loose and fluffy microbial aggregates in which filamentous bacteria were dominant. The intermittent feeding (Period II) allowed obtaining the succession of feast and famine conditions that favored the increase in AGS stability. Although no further breakage occurred, the formation of new granules was very limited, owing to the absence of the hydraulic selection pressure. These results noted the necessity to ensure, on the one hand the succession of feast/famine conditions, and on the other, the hydraulic selection pressure that allows flocculent sludge washout. This preliminary study shows that the proposed configuration could meet the first aspect; in contrast, biomass selection needs to be improved.